Bullying and cyberbullying: overlapping and predictive value of the co-occurrence - del Rey, Rosario; Elipe, Paz; Ortega-Ruiz, Rosario (Psicothema, 2012)
Several studies show certain co-occurrence of the traditional bullying and the cyberbullying. However, the results about relation and homogeneity among the roles of each of them are not unanimous. The present study intends to advance in the knowledge about the above-mentioned co-occurrence by exploring the dimensions of victimization and traditional aggression and cyber-victimization and cyber-aggression and by identifying its eventual directionality. A short-term longitudinal design was developed. The sample was formed by 274 adolescents, aging 12 to 18 years-old, belonging to 2 schools of Andalusia (South of Spain). In order to value the impact of bullying and cyberbullying the European Cyberbullying Intervention Project Questionnaire (ECIPQ) and the European Bullying Intervention Project Questionnaire (EBIPQ) were used. The results show important simultaneity among both phenomena and suggest that although in cyberbullying -cyber-victimization and cyber-aggression- may be predicted because of previous involvement of the subject in traditional bullying, on the contrary it does not happen. In addition, previous victimization is a risk factor for traditional bullying and for cyberbullying. Results are discussed in relation to the process and socio-group dynamics arising from the bullying and cyberbullying phenomena, and in terms of their prevention.